2015
DOI: 10.1007/s00423-015-1328-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon perspectives on the use and effects of neoadjuvant chemoradiation in the treatment of rectal cancer: a comprehensive review of the literature

Abstract: The initial benefit of adjuvant therapy in the treatment of rectal cancer patients became evident with prospective studies demonstrating improvements in various oncologic survival outcomes. Due to the improved compliance and reduced toxicity, as well as the potential for tumor down-staging and sphincter preservation, neoadjuvant approaches became the preferred method of administering chemotherapy and radiation. Furthermore, a subgroup of patients has been shown to present with complete clinical response to neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Additionally, although NCRT can help distal rectal cancer patients avoid excision of the anal sphincter, a notable proportion of patients required APR and permanent colostomies. However, even patients who undergo LAR to keep the anal sphincter have high rates of incontinence, anal mucus loss, anal blood loss, and daily pad use [3436]. A modest but significant proportion of patients who have completed NCRT and have sustained cCR may be able to avoid radical surgery and associated complications if a wait-and-see policy is employed, although some of these patients may still require salvage radical surgery because of LR or DM [37].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although NCRT can help distal rectal cancer patients avoid excision of the anal sphincter, a notable proportion of patients required APR and permanent colostomies. However, even patients who undergo LAR to keep the anal sphincter have high rates of incontinence, anal mucus loss, anal blood loss, and daily pad use [3436]. A modest but significant proportion of patients who have completed NCRT and have sustained cCR may be able to avoid radical surgery and associated complications if a wait-and-see policy is employed, although some of these patients may still require salvage radical surgery because of LR or DM [37].…”
Section: Discussionmentioning
confidence: 99%
“…For rectal cancers, the optimal interval to surgery with neoadjuvant chemoradiotherapy or adjuvant radiotherapy has not been established, although the Royal Marsden Hospital trial is evaluating results and the French Greccar 6 trial has recently reported on intervals ranging from 6 to 12 weeks . In the Greccar trial, there was a significant increase in the overall morbidity rate in the 11‐week group (as compared with the 7‐week group) due to complications .…”
Section: Discussionmentioning
confidence: 99%